Does millennials have an investment interest? theory of planned behaviour perspective - Noni Setyorini; Ika Indriasari (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2020)
This study aims to determine the effect of attitudes, subjective norms, and perceived behavioral control of interest in investing. This research use theory of planned behavior to explain how behavior is formed through attitudes, subjective norms, and perceived behavioral control in taking investment decision. This research uses online survey data collection methods. Sampling uses the convenient sampling method. Data (questionnaire) which can be used as many as 100 data and using multiple regression analysis as the test tool. The results showed that the attitude variable has not a significant effect towards investing interest in the capital market, while subjective and perceived norms behavioral control has influenced investment interest in the capital market. Based on the research findings, it is advisable to use persuasion that emphasizes the involvement of those closest to potential investors. In addition, seminars organized by IDX and the government will greatly help increase investor knowledge, thereby increasing one's investment power control.